De deconstructie van constructieve journalistiek op de VRT - de Smaele, Hedwig; Demeyere, Louis; Van Elsen, Kirsten (Tijdschrift voor Communicatiewetenschap, 2019)
The deconstruction of constructive journalism at VRT We contribute to the deconstruction of constructive journalism by suggesting a definition as well as an operationalization. We set up a measuring instrument that lists the characteristics and practices of constructive journalism and put it to the test. We conducted both a qualitative and quantitative content analysis of the 7 p.m. news bulletin of public broadcaster VRT under chief editor Björn Soenens (November 2013-September 2016). Soenens presented himself as a proponent of constructive journalism, but our findings show he was not able to implement his ideas into practice. News items under Soenens are found to be less constructive than news items under his predecessor Wim Willems. Our findings also suggest that ‘the layer of constructivity’ added to the news can be studied pre-eminently on the level of full coverage of a topic rather than on the level of any individual news item.
Keywords: content analysis